Integration of Artificial Intelligence and GIS: An Application Study Based on Machine Learning Random Forest and SHAP - Li, Feng (International Journal of Computer Science and Information Technology, 2026)
The integration of Geographic Information System (GIS) technology with artificial intelligence opens up innovative pathways for geospatial analysis. This study provides theoretical support and practical guidance for the deep integration of GIS and artificial intelligence, contributing to the advancement of geospatial analysis towards intelligence-driven approaches. With the evolution of GIS technology and the widespread adoption of artificial intelligence, The integration of Geographic Information System (GIS) technology and artificial intelligence has opened innovative paths for geographic spatial analysis. This study provides theoretical support and practical guidance for the deep integration of GIS and artificial intelligence, facilitating the move towards intelligent geographic spatial analysis. With the evolution of GIS technology and the widespread adoption of artificial intelligence, this research explores their innovative fusion in geographic spatial analysis. It focuses on the potential applications of the SHAP model in land use change prediction, environmental risk assessment, and urban planning, covering stages such as data preparation, model construction, interpretation, and spatial visualization. The results show that the SHAP model can effectively analyze the decision-making mechanisms of machine learning models and intuitively present the impact of geographic factors through spatial visualization.